Книжники-старообрядцы из пижемского рода Бобрецовых - Волкова, Татьяна (Acta Neophilologica, 2019)
This article analyses online database resources concerning the creators and followers of the 18th-20th centuries manuscript writing traditions in the present day region of Ust-Tsilma in the Komi Republic, in villages situated along the Pechora River and its tributaries, the Pizhma River and the Tsilma River. The analysis focuses on the materials concerning the Old Believers’ bibliophiles from the Bobretsov family who lived in Pizhma. They greatly contributed to preserving book collections in the region. There are 22 such people known, among whom owners of manuscripts collections and readers of old books can be found, including the writer A.F. Bobretsov, the author of Books as Keepsakes, a book in which he describes his being a sailor on the tsarist yacht “The North Star” in 1893-1899.